TREND FASHION HIJAB TERHADAP KONSEP DIRI HIJABERS KOMUNITAS HIJAB MEDAN - Khairun Nisa; Rudianto Rudianto (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2017)
His study aims to to see how trend fashion truth of the community hijab medan and to know the factors that encourage trend fashion hijab to the concept of self hijabers community hijab medan. This research uses the method descriptive qualitative to technique data collection in research which is through a method of interviews and observation in the research locations. Based on the research done obtained the result that hijab not only are mandatory for muslim women but truth is also a trend which had much cache by the muslim women and able to provide picture to the community of what the concept of muslim women in accordance with the teachings and the principle of islamic. Keywords: trend fashion , the concept of self , hijabers